2013
DOI: 10.1371/journal.pbio.1001621
|View full text |Cite
|
Sign up to set email alerts
|

Linking Stochastic Fluctuations in Chromatin Structure and Gene Expression

Abstract: Electron microscopy of single gene molecules and mathematical modeling shows that a promoter stochastically transitions between transcriptionally favorable and unfavorable nucleosome configurations, providing a mechanism for transcriptional bursting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
200
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(216 citation statements)
references
References 55 publications
13
200
2
1
Order By: Relevance
“…1B) and genome-wide micrococcal nuclease (MNaseseq) were performed (Fig. 1C), confirming previously reported nucleosome positioning on the PHO5 promoter for positions of the +1 through −3 nucleosomes of the PHO5 promoter under phosphate-rich conditions, which is nonpermissive for gene expression (30,(32)(33)(34)(35).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1B) and genome-wide micrococcal nuclease (MNaseseq) were performed (Fig. 1C), confirming previously reported nucleosome positioning on the PHO5 promoter for positions of the +1 through −3 nucleosomes of the PHO5 promoter under phosphate-rich conditions, which is nonpermissive for gene expression (30,(32)(33)(34)(35).…”
Section: Resultssupporting
confidence: 89%
“…1C). The majority of these cells had a −2 nucleosome occluding the high-affinity UAS, as previously shown by other methods (30,(32)(33)(34)(35). However, the single-cell analysis showed that about 10% of cells do not have a nucleosome over the highaffinity UAS (Fig.…”
Section: Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…Mais elles caractérisent aussi les cellules des organismes pluricellulaires, en particulier les cellules souches, qui présentent une expression générali-sée et très variable de leur génome [14]. Des études ont montré la relation entre la structure de la chromatine et le niveau de variabilité d'expression des gènes [15]. Dans le cas du cancer, les variations épigéné-tiques ont donc très certainement un impact sur ce phénomène (Figure 2).…”
Section: Les Variations Aléatoires De L'expression Géniqueunclassified